Analysis of nutritional policies implemented to tackle the double burden of under-five malnutrition in Zambia: a case study of Levy Mwanawasa University Teaching Hospital, Lusaka - Tuishime, Christopher; Kazonga, Eustarckio (International Journal Of Community Medicine And Public Health, 2025)
Background: This study analyzed the global nutritional policies to tackle the double burden of under-five malnutrition, and this was a case study of Levy Mwanawasa university teaching hospital in Lusaka. The main objective was to analyse the nutritional policies implemented to tackle the double burden of malnutrition at Levy Mwanawasa university teaching hospital. Methods: Qualitative phenomenological study methodology was used to identify the key elements of the nutritional policies implemented. The qualitative data gathered was analyzed using thematic analysis using Nvivo 14 software for data analysis. One-on-one interviews using a structured interview guide were conducted on 12 purposively selected participants that were enrolled in the study. Results: The results from the thematic data analysis produced three themes with regard to effectiveness of the adopted policies which are low level effectiveness, medium level effectiveness and high-level effectiveness. The major theme being medium effectiveness. With regard to challenges the themes that emerged were lack of knowledge among individuals on nutritious foods, healthy foods are expensive, lack of policy for regulate food market pricing and lack of information of nutritious foods which was the major theme. The main themes emerging from the suggestions were government regulation of food pricing, government help of orphans and vulnerable children with food handouts and government regulation of food market prices. Conclusions: The level of implementation of the adopted policies to address the double burden of malnutrition was medium. The study also suggested that the major challenge in the implementation was that individuals lack information on nutritious foods.